Cultivar Repair of Local Vigna Radiata L to Use Multigamma Irradiation Technique (Nuclear) That Tolerant to Dry Condition, Rainy Season, Germ, and High Production - Bartholomeus Pasangka; Irvandi Gorby Pasangka; Zoran S. Ilic (Postgraduate, University of Mataram, 2021)
Vigna Radiata L is grouped as the third important legume in Indonesia after soybean and peanut with high nutrition. The research aims to develop local Vigna Radiata L from Timor Island Indonesia with multi-gamma irradiation technique and carefully selection for obtaining several variations of superior varieties. The main research method comprised of observation, irradiation, purifying, careful selection, comparative, analysis, and interpretation. The results of research on final purifying are obtained three variations of mutant varieties with several superior chemical and physical characteristics.Â The production of Vigna Radiata L as a result of Multigamma irradiation significantly increased, and on final purifying obtained especial superior of selected mutant varieties namely, two varieties can be fruited for the second time with harvest age are relatively short